Hubungan Antara Citra Raga dengan Persepsi Terhadap Produktivitas Sales Promotion Girls Kosmetik Kecantikan di Kota Denpasar - Antari, Ayu Paramita; Tobing, David Hizkia (Jurnal Psikologi Udayana; Vol 1 No 2 (2014)DO - 10.24843/JPU.2014.v01.i02.p12, 2014)
The increasing sales of cosmetics beauty products make the product marketing technique expanding and  many sales promotion girl are employed to be important part in promoting women beauty product. Attractive physical appearance in sales promotion girls will draw consumer attention to them. Physical appearance itself correlates with body image in sales promotion girls. According Konstanski (2007) body image will be affected to self confidence. Self confidence makes a person develop self-evaluation. The self-evaluation will shape perceptions of productivity. According to that, researcher wants to find relationship between body image and perception of productivity in sales promotion girls of beauty product in Denpasar City.   Method in this research is correlational study. Subjects in this research are 110 sales promotion girls in Denpasar City. Data are collected by body image scale and perception of productivity scale.  Test of item validity in body image scale shows there are 27 invalid items and 23 valid items from 50 items, and its reliability coefficient is 0,829. Test of item validity in perception of productivity scale shows there are 2 invalid items and 23 valid items from 25 items, and its reliability coefficient is 0,838. Data analysis shows data are normal and linear. Pearson’s product moment is run for data analysis.   Coefficient of correlation between body image and productivity is 0,49 in significance level 0,05. It means that hypothesis in this research that states there is relationship between body image and perception of productivity in sales promotion girls of beauty product in Denpasar City is accepted.   Keyword: body image, perception of productivity, sales promotion girls